(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
From a young age, Mahadevi Verma had a deep love for reading and studying. From an earlyage on, she showed a keen interest in old texts and literature, and she became an expert in Hindi poetry.The Prayag Women’s University (Prayag Mahila Vidyapeeth) in Allahabad is where she earned herMaster’s degree in Sanskrit.Mahadevi Verma, an educator, pushed for equal educational opportunitiesfor women. She fought for equal educational opportunities for women and men in the early 20th century,when doing so was not popular. It was her fervent conviction that empowering women via education wascrucial to societal development as a whole. Examine the views of education reformer Mahadevi Verma inthis paper.